Consequences of Teachers’ Quality on Students’ Outcomes in Technical and Vocational Colleges in Lagos Nigeria (Journal of Didactic Studies, 2024)
This study aimed to investigate the influence of teachers’ quality on students’ outcomes in technical and vocational colleges. Two research questions and two hypotheses were tested at 0.05 level of significance. The Ex-post facto research design was used for the study, the population of the study was 223 students. The sample of the study was 85 undergraduate students. The collected data was analysed using the mean for the research questions and ANOVA to test the hypotheses. The result revealed that the teachers’ quality related to sex and certification does not have any significant influence on students’ outcomes in technical and vocational colleges. The recommendation was made that the government should recruit competent teachers for technical and vocational college teaching, there should be no consideration in the recruitment of technical and vocational teachers because the students’ outcomes are not related to teachers' sex and certification.